Characteristics and Management of Laryngopharyngeal Reflux in The Elderly : A Case Report - Ikhsan, Wahyu; Hidayati, Aliyah (Universitas Airlangga, 2024)
Laryngopharyngeal reflux is a condition resulting from the retrograde flow of stomach acid through the distal esophagus into the laryngopharyngeal area. The prevalence of laryngo-pharyngeal reflux in the elderly population remains uncertain. Therefore, the symptoms, findings, and therapy for laryngopharyngeal reflux in the elderly require further investigation. To analyze the characteristics and management of laryngopharyngeal reflux in the elderly. A case of laryngopharyngeal reflux in a 70-year-old woman who frequently experiences sudden choking sensations is presented in this report. Other symptoms include hoarseness, a sensation of throat obstruction, and chest burning. We explored literature on laryngopharyngeal reflux in the elderly through PubMed, PMC, and Google Scholar databases to discuss the case. Laryngopharyngeal reflux in the elderly has a lower reflux symptoms index but a higher reflux finding score. Mental health factors significantly influence laryngopharyngeal reflux incidence in the elderly. Therefore, besides pharmaco-logical therapy, additional non-pharmacological therapies need to be considered to ensure effective laryngopharyngeal reflux treatment. Elderly patients diagnosed with laryngopharyngeal reflux have different presentations and management of the disease compared with younger patients.